E-business maturity: constraints associated with their evolution - Morais, Elisabete Paulo (2012)
To compete effectively in the e-business world, an organization must structurally transform its internal foundation. This structural change requires an organization to develop an innovative e-business strategy, focusing on speed to market and breakthrough execution. Despite the recognition and care that in recent years has been dedicated to e-business, there remains a need for continuing research efforts that seek to better understand constraints on the evolution of an organization to a state that can take advantage of e-business possibilities. There is a special need for this when considering small and medium enterprises, or businesses in developing countries. To minimize risk exposure from e-business initiatives, it is imperative for an organization to identify potential constraints on e-business evolution. In this setting,we develop a research model that involves e-business constraints and e-business maturity. We classify the constraints into the categories of environment constraints, organizational constraints, and technological constraints. Our results indicate that there are constraints that can be more or less problematic, depending on the stage of maturity. The results are also quite different in large organizations versus Small and Medium Enterprises.